10-Gingerol reduces cytoplasmic lipid droplets and induces lipolysis in 3T3-L1 adipocytes - María Elizabeth Preciado-Ortiz; Erika Martínez-López; Trinidad García-Iglesias; Gildardo Gembe-Olivarez; Nathaly Torres-Castillo; Iris Monserrat Llamas-Covarrubias; Juan José Rivera-Valdés (Adipocyte)
Obesity is a globally prevalent metabolic disorder characterized by an increased number of adipose cells and excessive fat in adipocytes. Herbal medicines, such as ginger, have shown potential in treating obesity by inhibiting adipogenesis and reducing adipocyte hypertrophy. Ginger contains bioactive compounds, particularly gingerols, which have demonstrated anti-adipogenic and/or lipolytic effects. However, research on the effects of 10-gingerol on adipose tissue remains limited. This study aimed to evaluate the effect of 10-gingerol on lipid content, lipolysis markers, and the expression of genes related to lipid metabolism in 3T3-L1 adipocytes. Three groups were analyzed: a negative control (preadipocytes), a positive control (mature adipocytes), and a group treated with 10-gingerol (10-G). Results showed that 10-G reduced lipid accumulation by 42.16% in mature adipocytes compared to the control, without affecting cell viability. Additionally, 10-G increased glycerol release and downregulated lipogenic genes such as Pparγ, Acaca, Fabp4, and Mtor, while upregulating genes related to fatty acid oxidation, including Cebpα, Cpt1a, Lipe, and Prkaa1. In conclusion, 10-gingerol reduces lipid content in mature adipocytes by downregulating lipogenesis, increasing lipolysis, and enhancing fatty acid oxidation.